Biomass carbon accumulation by Japan's forests from 1947 to 1995 - Fang, Jingyun; Oikawa, Takehisa; Kato, Tomomichi; Mo, Wenhong; Wang, Zhiheng (Global Biogeochemical CyclesGlobal Biogeochemical Cycles, 2005)
Forest ecosystems in the Northern Hemisphere function as carbon (C) sinks for atmospheric carbon dioxide; however, the magnitude, location, and cause of the sinks remain uncertain. A number of field measurements of forest biomass and systematic national forest inventories in Japan make it possible to quantify the C sinks and their distribution. Allometric relationships between forest biomass and stem volume were obtained for the major forest types in Japan from 945 sets of direct field measurements across the country. These relationships were used to estimate the changes in C accumulations of aboveground biomass and total living biomass from 1947 to 1995 from the national forest inventories of 1947, 1956, 1961, 1965, 1975, 1980, 1985, 1990, and 1995. The results showed that the C accumulations have significantly increased during the last 50 years. The C density (C stock per hectare) and total C stock of aboveground biomass increased from 27.6 Mg C/ha and 611.7 Tg C in 1947 to 43.2 Mg C/ha and 1027.7 Tg C in 1995, respectively, and those of total living biomass increased from 33.9 Mg C/ha and 751.8 Tg C in 1947 to 53.6 Mg C/ha and 1274.8 Tg C in 1995. These increases were remarkable during 1976–1995, with a net increase of 5.6 Mg C/ha and 369 Tg C for the C density and total living biomass. These results suggest that Japan's forest vegetation is a significant C sink. In the past 20 years, living vegetation has sequestered 18.5 Tg C annually, 14.6 Tg C of which was accumulated in aboveground biomass. The total C sink for the whole forest sector (including nonliving biomass) of Japan was estimated as 36 Tg C/yr if using the net change ratio of nonliving biomass C to living biomass C derived from the United States and Europe. On the basis of average C sink per hectare, Japan's forests have a higher sequestration rate (0.77 Mg C ha−1 yr−1) than the average of the other northern countries (0.14–0.19 Mg C ha−1 yr−1). The expansion and regrowth of planted forests are two major causes for this increased C uptake; planted forests contribute ∼80% of the total C sink in Japan. The suitable oceanic climate for fast forest growth and effective forest management practice may be the principal factors for such a large sink.
Keywords: 0315 Atmospheric Composition and Structure: Biosphere/atmosphere interactions; 0428 Biogeosciences: Carbon cycling; 1615 Global Change: Biogeochemical cycles, processes, and modeling; 1631 Global Change: Land/atmosphere interactions; biomass expansion factor (BEF); carbon sink and source; direct field measurement; forest carbon budget; forest inventory; Japan